Metal Halide Perovskite Single Crystals toward Electroluminescent Applications - Wang, Chaoqiang; Chen, Shuai; Jie, Jiansheng; Tian, Chao; Jia, Ruofei; Wu, Xiaofeng; Zhang, Xiaohong; Zhang, Xiujuan (Advanced functional materials, 2025)
Metal halide perovskite single crystals (MHP SCs) have attracted extensive attention due to their superior properties, such as higher carrier mobility, longer carrier diffusion length, and better stability than their polycrystalline counterparts. In particular, the suppression of ion migration and Auger recombination endows MHP SCs with excellent electroluminescence (EL) properties, thus holding great potential for highly efficient and stable light‐emitting devices. In this review, general overview of MHP crystal structures are begin, and highlight the merits of MHP SCs in terms of outstanding optoelectronic properties and high stability. Then, appropriate growth methods of high‐quality, thickness‐controlled MHP SCs for EL device applications are systematically summarized. Subsequently, recent advancements in developing MHP SC‐based perovskite light‐emitting diodes (PeLEDs) are discussed, and the effective strategies to further enhance the device performance are reviewed. Moreover, the potential application of MHP SCs for electrically pumped lasers is highlighted. Finally, the review is concluded with a detailed account of the current challenges and a perspective on the key approaches and opportunities on the optimization of SC growth, the improvement of device performance and the integration of SC‐based optoelectronic devices. Metal halide perovskite single crystals (MHP SCs) have attracted much attention due to their dramatically enhanced optoelectronic properties and improved stability compared with their polycrystalline counterparts. The recent advancements in MHP SC‐based light‐emitting diodes, potential strategies for further device performance improvement and future application prospects in electrically pumped lasers are discussed in this review.